42nd AIAA Thermophysics Conference 2011
DOI: 10.2514/6.2011-3495
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Fluids-Radiation Analysis of a High-Mass Mars Entry Vehicle

Abstract: The NEQAIR line-by-line radiation code has been incorporated into the DPLR Navier-Stokes flow solver such that the NEQAIR subroutines are now callable functions of DPLR. The coupled DPLR-NEQAIR code was applied to compute the convective and radiative heating rates over high-mass Mars entry vehicles. Two vehicle geometries were considered -a 15 m diameter 70-degree sphere cone configuration and a slender, mid-L/D vehicle with a diameter of 5 m called an Ellipsled. The entry masses ranged from 100 to 165 metric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…As a rule of thumb, when Γ > 0.01, it generally indicates that the flow is strongly coupled [38]. For the condition being studied, stagnation-point radiative heat flux was calculated to be 3410 W ⋅ cm −2 via a tangent slab approximation, based on stagnation line temperatures and species number densities calculated and described in Sec.…”
Section: B Radiation Modelingmentioning
confidence: 99%
“…As a rule of thumb, when Γ > 0.01, it generally indicates that the flow is strongly coupled [38]. For the condition being studied, stagnation-point radiative heat flux was calculated to be 3410 W ⋅ cm −2 via a tangent slab approximation, based on stagnation line temperatures and species number densities calculated and described in Sec.…”
Section: B Radiation Modelingmentioning
confidence: 99%
“…In recent years, a number of studies have been performed to determine the vehicle and mission requirements that would enable the human exploration of Mars [1][2][3][4]. High-mass crewed Mars vehicles would be larger than previously-flown unmanned robotic spacecraft and would experience higher levels of radiative heating.…”
Section: Introductionmentioning
confidence: 99%
“…if the coupling is neglected. The dependance of the ratio between the actual radiative eating and what it would be if the flow was adiabatic q r /q r ad and the Goulard number Γ has indeed been demonstrated numerically or used by various authors (see for example [42,65,80,125,136,141,155,183,188,186,210]). As depicted in figures 4.1 for different atmospheres, the function linking both (using the logarithm of Γ) can be expressed in the form of a sigmoïd: decreasing from a certain value slightly smaller than 1.0 for uncoupled flows down to another constant value for fully-coupled flows.…”
Section: Non-adiabatic Radiative Heat Fluxmentioning
confidence: 81%
“…For example, Hollis et al suggest to use the same a = 3 for Titan atmospheric entry [80], as do Palmer et al for Mars entry due to the preponderance of CO [141]. Additional radiation coupling studies for Titan can be found in [136,183].…”
Section: Non-adiabatic Radiative Heat Fluxmentioning
confidence: 99%